"Double transformations:" nation formation and democratization in interwar East Central Europe. Issue 5 (10th January 2019) - Hein-Kircher, Heidi; Kailitz, Steffen
Abstract : Following the collapse of empires and the subsequent founding of self-determined nation-states, East Central Europe experienced a turning point after World War I. The new states had to transform themselves from branches of a multi-ethnic empire to independent nation-states, as well as from a system of monarchy to democracy at the same time. We argue that one cannot really understand why democracy failed in almost all East Central European states after World War I if one does not take into account the extreme challenges of this "double transformation" consisting of the interactions of the two tightly interwoven processes of nation formation and democratization. Therefore, we deem it necessary to develop a broader research program that addresses the complex interlacement of these two fundamental transformations of politics and society.